Influence of zinc ion concentration on structure, morphology, and optical properties of spray deposited ZnO thin films - Sarika Jadhav; Limbraj S Ravangave (Institute of Advanced Engineering and Science, 2021)
Zinc oxide (ZnO) thin films were deposited for five different molarity (M) of Zinc acetate hydrated (0.075, 0.1, 0.125, 0.15, and 0.175 M) using simple spray technique to study the effect of zinc ion concentration on structure, morphology, and optical properties. The XRD patterns of deposited ZnO thin films show hexagonal crystal structure with wurtzite symmetry. The effect of molarity on morphology was studied using scanning electron microscopy (SEM). The elemental analysis was studied by using energy dispersive X-ray analysis (EDX). The optical absorption was recorded by using systronics double beam spectrophotometer (2201). Crystallite size estimated from XRD data was in nanometre (nm) range; however, films deposited for 0.15 M zinc acetate show maximum crystallite size (66 nm) as compared to other samples. All the films show low absorption in wide range (340-999 nm) of electromagnetic spectrum. However, ZnO film deposited for 0.15 zinc acetate hydrated shows maximum blue shifting of absorption edge and higher band gap (3.8 eV) as compared to other samples.